Are Economic Sanctions a Barrier to Trade in Environmental Goods? The International Evidence - Ha, Tran Manh; Thang, Doan Ngoc (The Economics and Finance Letters, 2022)
The purpose of economic sanctions is to isolate a sanctioned country and harm its economy to force its government to adjust course, policies, and actions. To resist sanctions, a sanctioned country needs to adopt a variety of survivalist and unsustainable policies that undermine the economic challenge of sanctions at the expense of lowering priority to the environmental sector and the production of environmental goods (EGs). Due to the shortage of EGs in the sanctioned nations, we hypothesize that economic sanctions are a potential driver of trade in EGs. To assess the empirical merits of our theoretical claims, we used panel data with 5,297 pairs of 88 countries for the years spanning 1996 to 2019, inclusive. While economic sanctions take various forms, EGs refer to environmental goods and services that are manufactured, consumed, and disposed of without causing unintended environmental impacts. We used the Combined List of Environmental Goods (CLEG) to define the EGs. Our empirical results indicate that imposition of economic sanctions hinders trade in EGs. We also found clear evidence that the effect becomes more pronounced for the use of trade and financial sanctions and when the economic sanction is put on low-income countries.